THE EFFECT MEANS GYMNASTICS DEVELOPMENT OF AEROBIC FITNEES MOTRICE FORCE IN CHILDREN FROM SCHOOL - Coca Popovici Loredana Elena (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
Aerobics lesson has a strong formative, given its content, in addition to specific steps"aerobic and a variety of means taken from basic gymnastics, rhythmic sportive, semi acrobatics elements, steps of classical dance, modern, folk, dance - jazz. All these means to develop general physical, improve physical and mental condition of the participants. Learning these practical and theoretical knowledge will help the student to work individually at home. Aerobics lesson objectives coincide with the main objectives of aerobic gymnastics.